Linguistic Archeology of the Kirati Hydronyms - Rai, Tara Mani (Gipan, 2025)
This paper delves into the settlement patterns of the Kirati communities through the lens of linguistic archeology. The findings reveal that the hydronyms are not only the archeological evidence but also the indicator of the historical development and cultural ties. It focuses on the linguistic landscape of settlement and distribution of place names (toponyms), and water body names (hydronyms) across the Kirati indigenous communities. Employing a qualitative method, the study draws on both primary and secondary sources, including historical documents, linguistic data to examine the spatial and temporal dimension of migration and settlement. The key tools for data collection contains the ethnographic fieldwork, oral history recordings, interviews and the focus group discussion. The findings reveal that the analysis of the hydronyms in the Kirati languages bear the affixes < wa, ku kʰu, -ti>, indentifying the settelement pattern within the Kirati territories, extending into the Kathmandu valley. This furthe expands to the western part of Nepal, spcifically among the Magar with the suffix <-ti di>.